Middle East Refugee Crisis in Europe and Turkey : A Systematic Literature Review - Felicia Nabila Putri; Salahuddin; Syamsul Rizal; Gonda Yumitro (Journal of Islamic World and Politics, 2023)
This study aims to discuss how the European Union and Turkey deal with the Syrian refugee crisis. The research method used in this study was a systematic literature review using 504 scientific articles sourced from the Scopus database. In reviewing the articles, the authors used the Vosviewer application. The results revealed that Syrian refugees were accommodated correctly and facilitated properly and contributed to the problem by providing insight into digital literacy, information needs, and strategies among Syrian and Iraqi refugees entering Europe and changing perspectives on migrants and refugees as passive victims of this event made to make Syrian refugee decisions to stay in Germany, in an econometric strategy based on estimating models of equality in social unity, economic integration and the decision to stay. The results contribute to developing a research roadmap on the Syrian internecine crisis in Turkey and the European Union and contribute to international relations science. Turkey and the European Union. Subsequent research must use scientific articles from other reputable international databases, such as Web of Science and Dimensions Scholars.